2006
DOI: 10.3892/ijmm.17.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ down-regulates expression of tumor necrosis factor-α converting enzyme/a disintegrin and metalloproteinase 17 in activated hepatic stellate cells of rats

Abstract: Abstract. Interferon-Á (IFN-Á) is a potent cytokine that exerts antiproliferative and antifibrogenic effects on hepatic stellate cells (HSCs). Although therapeutic application of IFN-Á for chronic liver diseases is anticipated, the responses of activated HSCs to IFN-Á have not been fully elucidated. To seek unknown molecules and pathways that might be responsive to IFN-Á treatment in activated HSCs, we examined global protein expression profiles using two-dimensional gel electrophoresis combined with peptide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…According to the literature, we thought to evaluate the involvement of the two putative sheddases ADAM10 and ADAM17 that were highly expressed in our cells. Although the IFN-γ-dependent down-regulation of ADAM17 in rat HSC was recently reported by using a differential proteomic assay [19], the expression levels of ADAM10 and ADAM17 were not modified by IFN-γ treatment in human cultured HSC. Surprisingly, the specific inhibitor hydroxamate GW280264X that blocks ADAM10 as well as ADAM17 [15] partially affected the cleavage of CX3CL1 that was totally inhibited by batimastat suggesting the implication of another metalloprotease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, we thought to evaluate the involvement of the two putative sheddases ADAM10 and ADAM17 that were highly expressed in our cells. Although the IFN-γ-dependent down-regulation of ADAM17 in rat HSC was recently reported by using a differential proteomic assay [19], the expression levels of ADAM10 and ADAM17 were not modified by IFN-γ treatment in human cultured HSC. Surprisingly, the specific inhibitor hydroxamate GW280264X that blocks ADAM10 as well as ADAM17 [15] partially affected the cleavage of CX3CL1 that was totally inhibited by batimastat suggesting the implication of another metalloprotease.…”
Section: Discussionmentioning
confidence: 99%
“…As main source of matrix and proteases, the role of the profibrogenic hepatic stellate cells (HSCs) in this process has been well documented [17]. More recently, increased expression of members of ADAM family, including ADAM9, ADAM12 and ADAM17 was reported in patients with chronic liver diseases and expressed by the activated HSC [18][19][20][21]. In the present study, we investigated whether HSCs are involved in CX3CL1 shedding during liver injury.…”
Section: Introductionmentioning
confidence: 93%
“…In the context of IFN␥ biology, our work is consistent with previous studies emphasizing a number of IFN␥-regulated genes. Further, elucidation of such targets is critical for understanding IFN␥-mediated biological effects (1,3,29).…”
Section: Discussionmentioning
confidence: 99%
“…42 We have previously demonstrated that interferon-g treatment induces HSCs to downregulate ADAM17/TACE expression in association with phenotypic transformation and decreased secretion of TNFa, which is a representative cytokine that activates HSCs. 43 In addition, Mazzoca et al 31 have shown that ADAM9-S secreted from activated HSCs promotes the invasion of metastatic liver cancers. Locally elevated levels of AngII in HCC and background tissues (liver fibrosis) may affect stromal-tumor cell (HSC-HCC) interdependence, and contribute to tumor progression and liver dysfunction in patients with HCC.…”
Section: Figurementioning
confidence: 99%